Isaac Newton's Temple of Solomon and his reconstruction of sacred architecture - Morrison, Tessa; ebrary, Inc. (Basel : Birkhäuser, 2011)
In the 1680s Isaac Newton wrote the Philosophiae Naturalis Principia Mathematica. At the same time he was also working on a recreation of the plan of Solomon's Temple. In an unpublished manuscript entitled Introduction to the Lexicon of the Prophets, Part two: About the appearance of the Jewish Temple, or more commonly known by its call name Babson MS 0424, he described the architecture of the Temple. His main source for his recreation was the Book of Ezekiel, but he also used and compared it with a wide selection of Jewish, Classical, and contemporary sources, and he demonstrated a good knowledge and understanding of Vitruvius in his search for the truth of Solomon's Temple.
1 Introduction -- 2 Chronology, Prisca Sapientia and the Temple -- 3 Prophesy and the Temple -- 4 Prytanaeum and the Floor Plan of the Temple of Solomon -- 5 The Temple Measurements and the Sacred Cubit -- 6 An Overview of the Contents and the Source of Babson MS 0434 -- 7 Reconstruction -- 8 Conclusion
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: Newton, Isaac, -- 1642-1727; Jeruzalémský chrám (Jeruzalém); 10.-6. století př. Kr; 17. století; anglické rukopisy -- 17. století; chrámy -- Jeruzalém -- 10.-6. století př. Kr; starověká architektura -- Jeruzalém; stavební plány; historické prameny; biblické texty; architektura -- náboženské aspekty; English manuscripts -- 17th century; temples -- Jerusalem -- 10th-6th centuries B.C.; ancient architecture -- Jerusalem; building plans; historical sources; Biblical texts; architecture -- religious aspects; monografie; e-knihy online; monographs; e-books online